Dielectric properties of sub 20 nm homoepitaxial SrTiO3 thin film grown by molecular beam epitaxy using oxygen plasma. Issue 1 (25th January 2021) - Kim, Beomjong; Na, Byunghoon; Park, Jungmin; Kwon, Youngnam; Jeong, Myoungho; Lim, Hanjin; Yoon, Euijoon
Abstract: Epitaxial SrTiO3 thin films were grown by molecular beam epitaxy (MBE) using an oxygen plasma source. SrO and TiO2 layers were alternately deposited on 0.5 wt% (001) Nb doped SrTiO3 substrates whose surface were terminated with TiO2 . A two-dimensional (2-D) layer-by-layer growth mode was confirmed by the reflection high energy electron diffraction (RHEED) oscillation during the growth and the well-terraced SrTiO3 surface was obtained after growth. X-ray diffraction (XRD) and scanning transmission electron microscopy (STEM) analysis showed that the obtained SrTiO3 thin films had epitaxially (001) oriented and stoichiometric crystal structures without any interfacial layer. With simple MIS (Metal-Insulator-Semiconductor) capacitors using Ir top electrodes, the dielectric constants of the SrTiO3 thin film with 10, 15, 20, 100 nm were measured at room temperature, 10 kHz and zero bias.